Engaging telehealth to drive value-based urology. Issue 4 (July 2018) - Modi, Parth K.; Portney, David; Hollenbeck, Brent K.; Ellimoottil, Chad
Abstract : Purpose of review: Telehealth, or the remote delivery of healthcare services using telecommunications technology, has the potential to revolutionize the delivery of healthcare and contribute to ongoing efforts to provide high-value care. Recent findings: We discuss several categories of telehealth that have been applied to healthcare. Several of these approaches, in particular video visits and teleconsultations, have promising early data demonstrating the significant benefits of telehealth technology with respect to the quality of care, access, cost savings, and patient experience. Nonetheless, considerable knowledge gaps still exist regarding how and for which patients and diseases telehealth modalities should be applied. Finally, we discuss the barriers to widespread adoption at the institutional, state, and federal levels. Summary: Maximizing the value of healthcare is an important goal for hospitals, physicians, and policymakers. Telehealth leverages advances in technology and the widespread availability of telecommunications devices to make healthcare communication more available, more convenient, and more efficient for patients and providers. With appropriate policies and incentives, telehealth initiatives can improve the value of urologic care and smooth the transition to a value-based healthcare system.